2021
DOI: 10.3354/meps13746
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use of adult Pacific bluefin tuna Thunnus orientalis during the spawning season in the Sea of Japan: evidence for a trade-off between thermal preference and reproductive activity

Abstract: To examine the habitat usage of adult Pacific bluefin tuna (PBF), electronic tagging was conducted in the Sea of Japan during May and June of 2012-2017. Archival tags were internally implanted and pop-up satellite archival transmitting tags were deployed; data on the horizontal movements and diving behaviours of 36 individual PBF were successfully retrieved. In the summer spawning season, the tagged PBF were concentrated near Sado Island and Oki Island in the Sea of Japan, and they were distributed widely to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Kitagawa et al (2001), , Kitagawa et al (2007b) investigated λ for young PBT but estimated the values quite approximately and considered the difference between daytime and nighttime to be minor. Therefore, the difference presented here, i.e., higher in the daytime according to highly resolved, in situ sensing, is a new observation, although Fujioka et al (2021) reported that λ for adult fish increased when they experienced warm surface waters, probably to avoid overheating at night. In previous studies, bigeye tuna (T. obesus: BET), widely inhabiting temperate to tropical areas, was thought to modulate T b by changing the function of the rete mirabile to regulate cardiac output (Holland et al, 1992;Malte et al, 2007;Hino et al, 2021).…”
Section: Changes In Body Heat Insulation and Heat Production Rate In ...mentioning
confidence: 51%
“…Kitagawa et al (2001), , Kitagawa et al (2007b) investigated λ for young PBT but estimated the values quite approximately and considered the difference between daytime and nighttime to be minor. Therefore, the difference presented here, i.e., higher in the daytime according to highly resolved, in situ sensing, is a new observation, although Fujioka et al (2021) reported that λ for adult fish increased when they experienced warm surface waters, probably to avoid overheating at night. In previous studies, bigeye tuna (T. obesus: BET), widely inhabiting temperate to tropical areas, was thought to modulate T b by changing the function of the rete mirabile to regulate cardiac output (Holland et al, 1992;Malte et al, 2007;Hino et al, 2021).…”
Section: Changes In Body Heat Insulation and Heat Production Rate In ...mentioning
confidence: 51%